       Re: fullsimplify problem

• To: mathgroup at smc.vnet.net
• Subject: [mg52923] Re: [mg52908] fullsimplify problem
• From: Andrzej Kozlowski <akoz at mimuw.edu.pl>
• Date: Fri, 17 Dec 2004 05:18:33 -0500 (EST)
• Sender: owner-wri-mathgroup at wolfram.com

```What do you mean by " incorrect"? It's correct and  it's primary school
maths.

( - a / b^2) = =  ( + a / b^2) -> (2 a / b^2)==0 -> (a/b)*(2/b)==0 ->
(a/b)==0.

????????

Andrzej Kozlowski

On 16 Dec 2004, at 17:41, symbio wrote:

> Given ( - a / b^2) = =  ( + a / b^2), it can be written as (-2 a /
> b^2), but
> when I use FullSimplify on that equation, I get the incorrect result (
> a /
> b ) = = 0.  How is this possible?
>
> In:=
> -a/b^2 == a/b^2
> % // FullSimplify
> Out=
> \!\(\(-\(a\/b\^2\)\) == a\/b\^2\)
> Out=
> \!\(a\/b == 0\)
>
> In:=
> -2a/b^2 == 0 // FullSimplify
> Out=
> \!\(a\/b == 0\)
>

```

• Prev by Date: Re: please solve
• Next by Date: Re: please solve
• Previous by thread: Re: fullsimplify problem
• Next by thread: Re: fullsimplify problem